2021
DOI: 10.1021/acs.jpclett.1c03031
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Switching Behavior of a Perhydropolysilazane-Derived SiOx-Based Memristor

Abstract: SiO x is an important dielectric material layer for resistive switching memory due to its compatibility with complementary metal-oxide semiconductor (CMOS) technology. Here we propose a solution process for a SiO x dielectric layer based on perhydropolysilazane (PHPS). A series of SiO x layers with different compositions are prepared by controlling the conversion process from PHPS, then the resistance switching behaviors of typical Ag/SiO x /Au memristors are analyzed. The effect of oxygen vacancies and Si−OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…M emristors, featuring high nonlinearity, 1,2 low power consumption, 3,4 and continuously modulated conductance, 5,6 have made significant progress and breakthroughs ranging from memory-in logic, T-bit data storage, and bioinspired neuromorphic computing. 7−9 Memristive materials include three categories: oxides, 10,11 chalcogenides, 12,13 and organics.…”
mentioning
confidence: 99%
“…M emristors, featuring high nonlinearity, 1,2 low power consumption, 3,4 and continuously modulated conductance, 5,6 have made significant progress and breakthroughs ranging from memory-in logic, T-bit data storage, and bioinspired neuromorphic computing. 7−9 Memristive materials include three categories: oxides, 10,11 chalcogenides, 12,13 and organics.…”
mentioning
confidence: 99%
“…In order to more intuitively display the maximum HRS/LRS ratio under different scan voltage ranges, the relationship between the HRS/LRS ratio and the test voltage range is shown in Figure a. These parameters should be considered for the practical application of the memristor, including memory window, HRS/LRS ratio, and stability. , When the working voltage ranges from −1 to 1 V, the memory performance of sample D can meet the requirement of practical application. The first cycle I–V characteristic curve of sample D is shown in linear scale in Figure b, and the initial state (IS), HRS, and LRS of I–V characteristic curve were marked using different colors.…”
Section: Resultsmentioning
confidence: 99%
“…Memristors, an emerging nanoscale electronic device with unique superiority in ultrahigh data storage, memory logic applications, and neuromorphic computing, have been extensively examined by academia and industry. With a suitable permittivity (15–25) and a tunable oxygen vacancy (V o ) distribution, HfO 2 has been extensively investigated as a memristor. Chen et al reported that the HfO 2 -based memristor exhibited a bipolar resistive switching (BRS) with high cycling endurance (>10 10 cycles), a low SET/RESET voltage (<2.0 V), and a fast response time (<10 ns) .…”
mentioning
confidence: 99%
“…In this work, a reliable URS behavior is realized using a simple Ag/HfO x /Pt memristor structure. The memristor displays a retention time of >10 4 s, an ON/OFF ratio of >10 3 , and a good operation voltage. Synergy and competition between the Ag conductive filament formed by redox reaction and the migration of an oxygen vacancy are responsible for the observed URS.…”
mentioning
confidence: 99%